Physical Fitness Components in Relation to Attention Capacity in Latin American Youth with Overweight and Obesity - Fernandez-Vergara, O; Garcia-Hermoso, A; Hormazabal-Aguayo, I (Blackwell Munksgaard, 2020)
The aim of the study was twofold: (a) to examine the association between health-related physical fitness and attention capacity in Latin American children and adolescents with overweight and obesity and (b) to test whether body composition outcomes are moderators of this association. A cross-sectional design was used to study 201 overweight/obese participants (12.1 ± 2.1 years of age; 34.3% girls) from Chile (Active-Start study) and Colombia (HEPAFIT study). Body composition, muscular fitness, speed-agility, and cardiorespiratory fitness were evaluated using two similar test batteries (ALPHA and FUPRECOL). Attention capacity was measured by the d2 Test. Linear regression and moderation analyses were conducted. Linear regression analysis revealed an association between muscular fitness (β = 0.245, P =.015), speed-agility (β = −0.16, P =.027), cardiorespiratory fitness (β = 0.331, P <.001) and overall fitness score (β = 0.210; P =.004) and attention capacity (all analyses were controlled for age, sex, peak height velocity, maternal education, and study setting). Moderation analysis using the Johnson-Neyman technique revealed that the effect of the relationship between muscular fitness score and speed-agility and attention capacity was stronger as fat mass and fat mass index increased. In conclusion, physical fitness components are associated with higher attention capacity in youth with overweight/obesity, but body composition seems to moderate these relationships. Randomized controlled trials in this population would help to better understand whether improvements in different components of physical fitness lead to better attention capacity, especially in youth with excess adiposity. © 2020 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd